Merek UMKM, Aset Bangsa: Langkah Tegas Pemerintah Memperkuat Perlindungan Hukum - Frangky Radjak; Hijrah Lahaling; Sumiyati Beddu (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2024)
The importance of product brand protection for MSMEs is regulated by Undang-Undang Nomor 20 Tahun 2016 tentang Merek dan Indikasi Geografiswhich grants exclusive rights to registered trademark owners. However, awareness and participation of MSMEs in brand registration still need to improve, with only 175 trademark registration applications from 15,371 MSMEs in Gorontalo City. This study analyses the legal protection of rights to MSME product brands in Gorontalo City. A normative juridical approach is used in this study, with the analysis of primary, secondary, and tertiary legal materials. The study results show that socialization, education, and supervision are the government's preventive legal protections to prevent trademark infringement. In contrast, repressive legal protection is provided when there is a trademark dispute with a similarity in essence in the disputed trademark. This research is expected to make a theoretical and practical contribution to the development of MSMEs through adequate brand protection.